Individuals progressive tension protocol in the application of elastic bandage in nonspecific chronic low back pain: a case study - de Oliveira, Giani Alves; Del Antonio, Ana Carolina Ferreira Tsunoda; Stocco, Marieli Ramos; Del Antonio, Tiago Tsunoda; Andraus, Rodrigo Carvalho (Manual Therapy, Posturology & Rehabilitation Journal, 2021)
Introduction: Low back pain is a disorder of musculoskeletal origin of multifactorial character, which can become chronic when it persists for more than 3 months. It is expected that 80% of the world’s population will present with low back pain at some stage of life, characterizing it as a serious public health condition that requires specific interventions for treatment. Given the context, elastic banding arises, a resource that can be useful to these patients, however, its effectiveness requires that the bandage be of quality that the therapist has experience and that its application is standardized, the latter being scarce in the current literature. Thus, the present study sought to observe what would be the application of a progressive tension protocol with elastic bandage in an individual with nonspecific chronic low back pain. Methods: A 47-year-old female, caregiver of the elderly and diagnosed with nonspecific chronic low back pain participated in the study. The treatment protocol lasted 10 weeks, where the elastic bandage was applied to the participant and in the first and last session, in addition to the report of the level of pain obtained through the Numerical Pain Scale (END), the following questionnaires were used to evaluate: Oswestry Disability Index (ODI), Survey of Pain Attitude (SOPA-B) and Fear Avoidance Beliefs Questionnaire (FABQ). Conclusion: The findings suggest that the application of elastic bandage following the progressive tension protocol promoted a reduction in disability index, pain and fear of movement, such outcomes can be considered clinically relevant, given the constant search for therapeutic techniques that provide improvement in the quality of life of patients with chronic low back pain.